L'aide sociale et le prêt, les droits extrapatrimoniaux et l'assurance-chômage - Baillargeon, Christian (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1986)
This paper studies different aspects of a particular concept of social welfare, namely assistance in the form of a loan versus standard nonrefundable assistance. It begins with an historical and jurisprudential analysis of section 13 of the Social Welfare Act which allows this kind of loan. This background is essential for grasping the goals and the bearing of the Social Welfare Act. This study mainly covers two situations which have raised and still are raising numerous controversies. First, an analysis is made of conditions and prospects of people requesting a loan from Social Welfare while awaiting unemployment compensations. Second, the study focuses on important litigation between beneficiaries of Social Welfare who have been granted extrapatrimonial damages and how the interpretation to be given to section 13 of this Act has been administered. Not only is an attempt made to determine the Social Affaires Commission's standpoint on these two matters, but the study also assesses the view of the Civil courts. Finally, within the scope of this study, the latest amendments to section 13 are reviewed and commented upon.